Duplex Collecting System Unilateral Asimptomatik dengan Duplikasi Komplit Ureter di Ginjal Kanan: Temuan Computed Tomography Tiga Dimensi.: Laporan Kasus - Luh Made Deasy Dwitayanti; Putu Aditha Satya Putra; Kadek Budi Santosa (PT Kalbe Farma Tbk., 2024)
Introduction: Most people with ureteral duplications never experience any symptoms, so the condition goes unreported despite being one of the most prevalent kidney anomalies. Case: A 31-year-old female visited our medical facility for a routine checkup. Kidney function and complete urine analysis were normal. Ultrasonography revealed what appears to be a duplex collecting system in the right kidney, with two distinct noncommunicating renal pelvices. A 3D computed tomography (CT) scan of the abdomen with contrast revealed a duplex collecting system in the right kidney. Conclusion: Radiologists play a crucial role in detecting these abnormalities.